Comparative evaluation of the use of dry binders in a physical mixture or as a coprocessed dry binder in matrix tablets with extended drug release - Mužíková, Jitka; Komersová, Alena; Lochař, Václav; Vildová, Lucie; Vošoustová, Bára; Bartoš, Martin (Acta pharmaceutica (Zagreb, Croatia), 2018)
This paper evaluates and compares the properties of directly compressible tabletting materials and matrix tablets containing a combination of α-lactose monohydrate and microcrystalline cellulose in the 3:1 ratio in a physical mixture and in a coprocessed dry binder. Tested parameters include flow properties, compressibility, compactibility and the rate of drug release from tablets. Compressibility is evaluated by means of the energy profile of the compression process. Compactibility is evaluated by means of the tensile strength of the tablets. Dissolution testing is done using the rotating basket method. Dissolution profiles are evaluated by non-linear regression analysis. Total energy of compression and plasticity values were higher in tabletting materials with the coprocessed dry binder. Increasing additions of polyvinyl alcohol decreased the values of total energy of compression, plasticity, tensile strength of tablets and drug release rate. Dissolution behaviour of tablets, which contained the physical mixture or coprocessed dry binder and the same amount of polyvinyl alcohol, was comparable.
Keywords: farmaceutická chemie; celulosa; Salicylic Acid; pomocné látky; dissolution testing; laktosa; Lactose; Polyvinyl Alcohol; Tablets; Nonlinear Dynamics; Excipients; polyvinyl alcohol; matrix tablets; Cellulose; Chemistry, Pharmaceutical; farmaceutická technologie; rozpustnost; polyvinylalkohol; tensile strength of tablets; Technology, Pharmaceutical; kyselina salicylová; pevnost v tahu; Drug Liberation; tablety; coprocessed dry binder; nelineární dynamika; uvolňování léčiv; Tensile Strength; energy profile of compression; Solubility